Cancer-Derived Exosomal miR-651 as a Diagnostic Marker Restrains Cisplatin Resistance and Directly Targets ATG3 for Cervical Cancer. (16th September 2021) - Zhu, Xiaofan; Long, Ling; Xiao, He; He, Xuan
Abstract : Objective . Cancer-derived exosomes can facilitate drug resistance in cervical cancer. However, the mechanisms remain elusive. Herein, we observed the roles of exosomal miR-651 in cisplatin resistance of cervical cancer. Methods . Circulating miR-651 was detected in cervical cancer and healthy individuals. The diagnostic efficacy was determined. When transfected with miR-651 mimics, cisplatin resistance, apoptosis, and proliferation were assessed. The cancer-derived exosomes were separated and identified. We observed the uptake of PKH67-labeled exosomes by HeLa/S cells. After coculture with exosomes secreted by HeLa/S or HeLa/DDP cells, malignant behaviors were examined in HeLa/S cells. The interactions between ATG3 and miR-651 were validated by dual luciferase report. Biological behaviors were investigated for HeLa/S cells cocultured with exosomes secreted by miR-651 mimic-transfected HeLa/DDP cells. Results . Downregulated circulating miR-651 was found in cancer subjects than healthy individuals. It possessed high sensitivity and accuracy in diagnosing cervical cancer (AUC = 0.9050 ). Lower miR-651 expression was confirmed in HeLa/DDP than HeLa/S cells. Forced miR-651 lessened cisplatin resistance and proliferation and elevated apoptosis in HeLa cells. ATG3 was a direct target of miR-651. The exosomes isolated from HeLa cells were rich in CD63, CD9, and CD81 proteins, thereby identifying the isolated exosomes. Exosomes secreted by HeLa/DDP cells can be absorbed by HeLa/S cells. When being cocultured with exosomes secreted by HeLa/DDP cells, malignant behaviors of HeLa/S cells were enhanced, which were ameliorated by miR-651 mimic exosomes. Conclusion . Our findings showed that cancer-derived exosomal miR-651 restrained cisplatin resistance and directly targeted ATG3, indicating that exosomal miR-651 could be a therapeutic agent.